Key pre-distribution schemes to support various architectural deployment models in WSN. (2016) - Pramod, T.C.; Sunitha, N.R.
The tremendous applications of wireless sensor technology for day to day activities are rapidly increasing. They have the ability to make the environment smart and prolific. As vulnerabilities on wireless sensor networks are increasing, ensuring secure communication has gained a lot of attention from past years. In this paper, by considering the resource constraints of those networks, three deterministic key pre-distribution schemes are proposed using the symmetric matrix property to support group, grid and overlay based architecture deployment models. The proposed key pre-distribution schemes aim to minimise the key storage overhead and increase the local connectivity and resilience of the network.